Granulous KMS-1/PAN composite for Cs+ removal. Issue 111 (26th October 2015) - Wang, Yun-Xia; Li, Jian-Rong; Yang, Jia-Cheng E.; Yuan, Baoling; Fu, Ming-Lai
Abstract : A novel KMS-1/PAN composite was successfully fabricated simply by combining KMS-1 with PAN. The KMS-1/PAN combines the efficient, rapid adsorption of Cs + by KMS-1 with granulation for easy separation after adsorption. Abstract : A novel KMS-1/PAN composite was successfully and simply fabricated by combining KMS-1 with PAN. The KMS-1/PAN combines the efficient, rapid adsorption of Cs + by KMS-1 with granulation for easy separation after adsorption. The maximum Cs + adsorption capacity of KMS-1/PAN was estimated to be 72.00 mg g −1 according to the Langmuir model.